Public Finance in a Nutshell: A Cobb-Douglas Teaching Tool for General Equilibrium Tax Incidence and Excess Burden - Don Fullerton; Chi L. Ta (Center for Economic Studies and ifo Institute (CESifo), 2016)
To help first- or second-year graduate students in economics apply their theoretical training, this paper shows how to solve a simple and intuitive computable general equilibrium (CGE) model using a calculator. Because this simplified Harberger model uses Cobb Douglas functional forms for utility and production, one can solve for all input and output prices and quantities with no taxes and then solve for exact measures of output with a large tax change (not using derivatives). We then show how to solve simultaneously for capital and labor prices (incidence on the sources side of income), for both output prices (incidence on the uses side), for exact measures of overall welfare loss such as the equivalent variation, for excess burden and marginal excess burden, and for the effects on revenue in the form of a Laffer Curve.
Keywords: A20; C63; C68; D04; D58; H21; H22; H23; H24; H25; 330; computable general equilibrium; economic efficiency; distribution of burdens; sources side; uses side; equivalent variation